HIGH-LEVEL DISINFECTANTS ALTERNATIVE TO GLUTARALDEHYDE FOR PROCESSING FLEXIBLE ENDOSCOPES - Eliane Molina Psaltikidis; Mirtes Loeschner Leichsenring; Marlene Hitomi Yoshida Nakamura; Joaquim Murray Bustorff-Silva; Luis Augusto Passer; Sonia Isoyama Venâncio (Universidade Federal do Paraná, 2014)
Flexible endoscopes are fundamental in various medical specialities; in general they are heat-sensitive, semi-critical, and subject to high level disinfection. Glutaraldehyde is largely used for this purpose, due to its high compatibility and low-cost. However, its tolerance of mycobacteria and occupational toxicity lead to pressure being applied for the adoption of alternative germicides. A systematic review was undertaken aiming to seek evidence regarding the effectiveness, toxicity and potential harm caused to the endoscopes by those germicides which are alternative to glutaraldehyde and which are available on the market in Brazil. A total of 822 publications was identified in 13 electronic databases, between 2008 and 2013. Of these, 23 studies were selected, considering the best quality of evidence available. The publications point to the superiority of peracetic acid and of orthophthaldehyde regarding efficacy in high level disinfection. Only orthophthaldehyde presented an adverse event clearly related to its use. There is insufficient evidence to assert that any of these germicides has greater potential for harm to the equipment.